Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355